The Effect of Additional Magnesium Sulphate 80 mg with 0,5% Hiperbaric Bupivacaine to Onset and Duration of Action of Sensory and Motor Block Spinal Anaesthesia for Caesarean Section - , Suwarman; Purwaningsih, Sriwahyuniati; Nawawi, A. Muthalib; Yuwono, Hendro Sudjono (Majalah Anestesia dan Critical Care, 2015)
Addition of adjuvants to 0.5% hyperbaric bupivacaine for spinal anaesthesia performed to accelerate sensory and motor onset, minimal side effect of hemodynamics and prolongation analgesia. The aim of the study was to investigate the effect of additional 80 mg of magnesium sulphate 40% intratecal to 0.5% hyperbaric bupivacaine on onset and duration of sensory and motor block for cesarean section. The study was randomized double blind controlled study to 40 patients with American Society of Anesthesiology (ASA) physical status II whom underwent caesarean section in Dr. Hasan Sadikin General Hospital Bandung from April till May 2015. The additional 80 mg of 40% magnesium sulphate to 0.5% hyperbaric bupivacaine intratecal resulted earlier onset of sensory and motor block than group 0,9% sodium chloride (p˂0,001). The duration of sensory and motor block was longer in magnesium group than sodium chloride 0,9% group (p˂0,001). The study concluded that spinal anesthesia using 0.5% hyperbaric bupivacaine with magnesium sulphate produce faster onset and prolonged duration of sensory and motor blockade compared to 0.5% hyperbaric bupivacaine in cesarean section.